2013
DOI: 10.3233/jad-131139
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adipokine Levels Modified by Donepezil Treatment in Alzheimer's Disease

Abstract: Neurotransmitter enhancement therapy with acetylcholinesterase inhibitors (AChEIs) is a clinically proven approach for patients with Alzheimer's disease (AD). Donepezil is one of the three currently approved AChEIs for treating AD symptoms delaying the decline in cognitive function. In addition to cholinergic hypofunction, there are several factors in AD pathogenesis. For example, adipocytokines released from adipose tissue are also thought to play a role in the progress of dementia. Adipokines, i.e., leptin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Another study did not find any significant difference between individuals with AD and control subjects (Warren et al, 2012), whereas others found that serum levels of adiponectin were significantly lower in individuals with mild cognitive impairment (MCI) or AD compared with control subjects (Teixeira et al, 2013). In addition, in AD patients, donepezil, one of the currently approved treatments for AD, restored plasma adiponectin levels (Pákáski et al, 2014). In our study, adiponectin levels were significantly decreased in the plasma of Swiss Webster mice but not in C57 mice that did not experience learning deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Another study did not find any significant difference between individuals with AD and control subjects (Warren et al, 2012), whereas others found that serum levels of adiponectin were significantly lower in individuals with mild cognitive impairment (MCI) or AD compared with control subjects (Teixeira et al, 2013). In addition, in AD patients, donepezil, one of the currently approved treatments for AD, restored plasma adiponectin levels (Pákáski et al, 2014). In our study, adiponectin levels were significantly decreased in the plasma of Swiss Webster mice but not in C57 mice that did not experience learning deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Donepezil is one of the four acetylcholinesterase inhibitors that are marketed drugs for the symptomatic treatment of AD. Intriguingly, the serum adiponectin levels progressively increased in AD patients who were administered with Donepezil [91]. Adiponectin has been considered as a therapeutic target to treat metabolic syndromes because of its potent protective effects to both the CNS and peripheral tissues.…”
Section: Therapeutic Potential Of Adiponectinmentioning
confidence: 99%
“…Inhibition of tau aggregation may be an efficient strategy to inhibit sequestration of APN by tau, and a clinical study of tau immunization for progressive supranuclear palsy is ongoing 68. However, stimulating endogenous production of APN using compounds such as PPAR‐ γ agonists,69 acetylcholinesterase inhibitors,70 and vitamin E71 may be detrimental in terms of the toxic gain of function of APN.…”
Section: Apn As a Novel Target For Therapies For Admentioning
confidence: 99%